Synthesis and evaluation of thieno[2,3-d]pyrimidin-4(3H)-ones as potential antitubercular agents - Borate, Hanumant B.; Annadate, Ritesh A.; Vagh, Sandip S.; Pisal, Mahesh M.; Deokate, Sagar B.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Nawale, Laxman U.; Sarkar, Dhiman (MedChemComm, 2015)
A number of thieno[2,3-d]pyrimidin-4(3H)-ones were designed, synthesized and screened against Mycobacteria as a part of our program to develop new antitubercular agents. It was observed that some of the compounds have significant antimycobacterial activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743). The active compounds were studied for cytotoxicity against four cell lines and were found to be non-cytotoxic. The results showed that compounds 13b and 29e were found to exhibit very good antimycobacterial activity (MIC in the range of 6-8 mu M) and the thienopyrimidinones as a class have potential to be developed as antitubercular agents.

Synthesis and antitubercular activity of new 1,3,4-oxadiazoles bearing pyridyl and thiazolyl scaffolds - Dhumal, Sambhaji T.; Deshmukh, Amarsinh R.; Bhosle, Manisha R.; Khedkar, Vijay M.; Nawale, Laxman U.; Sarkar, Dhiman; Mane, Ramrao A. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of more potent and safe new antitubercular agents, here new 2-pyridinyl substituted thiazolyl-5-aryl-1,3,4-oxadiazoles (6a-o), have been designed and synthesized using thionicotinamide as a starting, following novel multistep synthetic route. An intermediate, pyridinyl substituted thiazolyl acid hydrazide (4) when condensed with benzoic acids/nicotinic acids (5a-o) in the presence of silica supported POCl3 yielded better to excellent yields of the title compounds. All the synthesized compounds (6a-o) and intermediate acid hydrazide (4) have been screened for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB) and Mycobacterium bovis BCG. Amongst them, 6f, 6j, 6l and 6o have revealed promising activity against M. bovis BCG at concentrations less than 3 mu g/mL. These compounds have shown low cytotoxicity (CC50: > 100 mu g/mL) towards four human cancer cell lines. Molecular docking study has also been performed against mycobacterial enoyl reductase (InhA) enzyme to gain an insight into the binding modes of these molecules and recorded good binding affinity. The ADME properties the title products have also been analyzed. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: 1; 3; 4-Oxadiazole; Antitubercular activity; Cytotoxicity; Molecular docking; Pyridine; Thiazole

Synthesis and antitubercular activity of new benzo[b]thiophenes - Mahajan, Pravin S.; Nikam, Mukesh D.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman; Gill, Charansingh H. (ACS Medicinal Chemistry Letters, 2016)
In vitro and ex vivo efficacies of four series of benzo[b]thiophene-2-carboxylic acid derivatives were studied against Mycobacterium tuberculosis H37Ra (MTB). Benzo[b]thiophenes were also tested in vitro against multidrug resistant Mycobacterium tuberculosis H37Ra (MDR-MTB), and 7b was found to be highly active against A- and DMDR-MTB/MTB (MIC ranges 2.73-22.86 mu g/mL). The activity of all benzo[b]-thiophenes against M. bovis BCG (BCG) was also assessed grown under aerobic and under conditions of oxygen depletion. Compounds 8c and 8g showed significant activity with MICs of 0.60 and 0.61 mu g/mL against dormant BCG. The low cytotoxicity and high selectivity index data against human cancer cell lines, HeLa, Panc-1, and THP-1 indicate the potential importance of the development of benzo[b]thiophene-based 1,3-diketones and flavones as lead candidates to treat mycobacterial infections. Molecular docking studies into the active site of DprE1 (Decaprenylphosphoryl-beta-n-ribose-2'-epimerase) enzyme revealed a similar binding mode to native ligand in the crystal structure thereby helping to understand the ligand protein interactions and establish a structural basis for inhibition of MTB. In summary, its good activity in in vitro and ex vivo model, as well as its activity against multidrug-resistant M. tuberculosis H37Ra in a potentially latent state, makes 7b an attractive drug candidate for the therapy of tuberculosis.
Keywords: Benzo[b]thiophene; Cytotoxicity; M. Bovis BCG; MDR-MTB; Molecular docking

Synthesis and evaluation of thieno[2,3-d]pyrimidin-4(3H)-ones as potential antitubercular agents (vol 6, pg 2209, 2015) - Borate, Hanumant B.; Annadate, Ritesh A.; Vagh, Sandip S.; Pisal, Mahesh M.; Deokate, Sagar B.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Nawale, Laxman U.; Sarkar, Dhiman (Medchemcomm, 2016)

Synthesis and biological evaluation of 1,2,4-triazole-3-thione and 1,3,4-oxadiazole-2-thione as anti-mycobacterial agents - Sonawane, Amol; Rode, Navnath D.; Nawale, Laxman U.; Joshi, Rohini R.; Joshi, Ramesh A.; Likhite, Anjali P.; Sarkar, Dhiman (Chemical Biology & Drug Design, 2017)
Resistance among dormant mycobacteria leading to multi-drug resistant (MDR) and extremely-drug resistant(XDR) tuberculosis is one of the major threats. Hence, a series of 1,2,4-triazole-3-thione and 1,3,4-oxadiazole-2-thione derivatives (4a-5c) have been synthesised and screened for their anti-tubercular activity against Mycobacterium tuberculosis H37Ra (H37Ra). Thetriazolethiones4b and 4v showed high anti-tubercular activity (both MIC and IC50) against the dormant H37Ra by in vitro and ex vivo. They were shown to have more specificity towards mycobacteria than other gram-negative and gram- positive pathogenic bacteria. The cytotoxicity was almost insignificant up to 100 μg/mL against THP-1, A549 and PANC-1 human cancer cell lines, and solubility was high in aqueous solution, indicating the potential of developing these compounds further as novel therapeutics against tuberculosis infection.

Synthesis and biological evaluation of new fluconazole β-lactam conjugates linked via 1,2,3-triazole - Divse, Jaisingh M.; Mhaske, Santosh B.; Charolkar, Chaitanya R.; Sant, Duhita G.; Tupe, Santosh G.; Deshpande, Mukund V.; Khedkar, Vijay M.; Nawale, Laxman U.; Sarkar, Dhiman; Pore, Vandana S. (New Journal of Chemistry, 2017)
Novel 1,2,3-triazole-linked β-lactam–fluconazole conjugates 12(a–l) were designed and synthesized. The compounds showed potent antifungal activity against two pathogenic Candida strains; Candida albicans ATCC 24433 and Candida albicans ATCC 10231 with MIC values in the range of 0.0625–2 μg mL−1. Compounds 12h, 12j and 12k showed promising antifungal activity against all the tested fungal pathogens except C. neoformans ATCC 34554 compared to fluconazole. Compound 12j in which the β-lactam ring was formed using para-anisidine and benzaldehyde was found to be more potent than fluconazole against all the fungal strains with an IC50 value of <0.015 μg mL−1 for Candida albicans (ATCC 24433). Mechanistic studies for active compounds revealed that the antifungal action was due to ergosterol inhibition. Compounds 12h and 12j at a concentration of 0.125 μg mL−1 caused 91.5 and 96.8% ergosterol depletion, respectively, compared to fluconazole which at the same concentration caused 49% ergosterol depletion. The molecular docking study revealed that all the fluconazole β-lactam conjugates 12(a–l) could snugly fit into the active site of lanosterol 14α-demethylase (CYP51) with varying degrees of affinities. As anticipated, the binding energy for compound 12j (−58.961 kcal mol−1) was much smaller than that for fluconazole (−52.92 kcal mol−1). The synthesized compounds have therapeutic potential for the control of candidemia.

Synthesis, antimycobacterial screening and molecular docking studies of 4-aryl-4′-methyl-2′-aryl-2,5′-bisthiazole derivatives - Abhale, Yogita K.; Shinde, Abhijit D.; Deshmukh, Keshav K.; Nawale, Laxman U.; Sarkar, Dhiman; Choudhari, Prafulla B.; Kumbhar, Santosh S.; Mhaske, Pravin C. (Medicinal Chemistry Research, 2017)
A series of 4-aryl-4′-methyl-2′-aryl-2,5′-bisthia- zole derivatives (5a–o) were synthesized and screened for inhibitory activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743) strains. Five lead compounds (5e, 5f, 5g, 5h, and 5o) were further confirmed from their dose dependent effect against MTB and Bovine–Calmette–Guerin. The most promising compounds 5f (MIC90: 11.32 μg/mL), 5h (MIC90: 11.59 μg/mL), and 5o (MIC90: 23.64 μg/mL) showed strong antitubercular activity against dormant MTB and BCG as well as almost insignificant cytotoxicity up to 100μg/mL against HeLa, A549, and PANC-1 human cancer cell lines. Further, the synthesized compounds were found to have potential antibacterial activity against Gram-negative bac- teria, Escherichia coli, Pseudomonas flurescence and Gram- positive bacteria, Staphylococcus aureus, Bacillus subtilis. Most of the synthesized compounds showed moderateactivity against fungal strain Candida albicans. Molecular docking studies of these compounds showed significant interactions with crystal structure of the cytochrome P45014α-sterol demethylase (CYP51) PDB ID: 1E9X. Hydrogen bond interactions with SER261 and VAL395 are important interactions for selective inhibition of designed inhibitors. Compounds 5f, 5h, and 5o showed significant interactions with 1E9X. All the experimental results promote us to consider this series as a starting point for the devel- opment of novel, selective and more potent antitubercular agents in the future.